Microcystic Variant of Urothelial Carcinoma. (2nd December 2013) - Venyo, Anthony Kodzo-Grey
Abstract : Background . Microcystic variant of urothelial carcinoma is one of the new variants of urothelial carcinoma that was added to the WHO classification in 2004. Aims. To review the literature on microcystic variant of urothelial carcinoma. Methods. Various internet search engines were used to identify reported cases of the tumour. Results . Microscopic features of the tumour include: (i) Conspicuous intracellular and intercellular lumina/microcysts encompassed by malignant urothelial or squamous cells. (ii) The lumina are usually empty; may contain granular eosinophilic debris, mucin, or necrotic cells. (iii) The cysts may be variable in size; round, or oval, up to 2 mm; lined by urothelium which are either flattened cells or low columnar cells however, they do not contain colonic epithelium or goblet cells; are infiltrative; invade the muscularis propria; mimic cystitis cystica and cystitis glandularis; occasionally exhibit neuroendocrine differentiation. (iv) Elongated and irregular branching spaces are usually seen. About 17 cases of the tumour have been reported with only 2 patients who have survived. The tumour tends to be of high-grade and high-stage. There is no consensus opinion on the best option of treatment of the tumour. Conclusions . It would prove difficult at the moment to be dogmatic regarding its prognosis but it is a highly aggressive tumour. New cases of the tumour should be reported in order to document its biological behaviour.